Toxicological evaluation of the red mold rice extract, ANKASCIN 568-R: 13-week chronic toxicity, and genotoxicity studies - Che-Wei Lin; Hsiao-Lin Chen; Yu-Hui Yang; Ya-Yuan Chen; Ya-Wen Hsu; Tzu-Ming Pan (Toxicology Reports, 2022)
ANKASCIN 568-R is an extract derived from red mold rice (RMR) fermented using Monascus purpureus NTU 568. RMR fermented using M. purpureus NTU 568 prevents cardiovascular diseases and decreases blood lipid levels. This study evaluates the safety of ANKASCIN 568-R, since it has not determined yet. After daily oral ANKASCIN 568-R for 13 consecutive weeks, we evaluated the toxicity tolerance of Sprague-Dawley rats and performed dose formulation analysis on monascin and ankaflavin. The dose formulation analysis showed that ANKASCIN 568-R concentrations were lower than the target concentration and out of range ( ± 15%) at week 8 and on the last dosing day for both monascin (all dose groups) and ankaflavin at the 100 mg/kg dose. The lowest reported concentrations for the low, middle, and high dose formulations were 34.7, 115.2, and 398.1 mg/mL, respectively. We also evaluated the genotoxicity of ANKASCIN 568-R and showed no genotoxicity potential at all ANKASCIN 568-R doses investigated. The no observed adverse effect level of ANKASCIN 568-R was determined to be 796.2 mg/kg/day. This study revealed the first toxicity evaluation data of ANKASICN 568-R, and the data demonstrated ANKASICN 568-R was safe and can be used in daily life.